Kelas Menengah Santri Dan Proses Demokratisasi di Indonesia - Agus Darmaji (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2018)
The theory of the relationship between the middle class and democratization has been a serious discussion since the latter half of the 1950s when Martin Lipset tried to examine the relationship between the two to find out the main requirements for the realization and maintenance of democracy in a country. Since the Lipset period, the debate on the relation between the middle class-democratization can be divided into two mainstream approaches, namely unilinear and contingent.The first group that uses a unilinear approach has a theoretical basis for the theory of modernization. This group argues that when modernization occurs in a society, the level of income, education, socioeconomic mobility, and views on the values of freedom will also increase. These things are in turn believed to encourage the creation of democratization in a society or country that is not yet democratic, and at the same time can strengthen democratic institutions in countries that have implemented democracy as their state system. Hattori concluded that the presence of the middle class generally encouraged, even they became the main pillars of the movement towards democratization. In simple terms this unilinearist group wants to say that modernization in the socioeconomic sector will foster the middle class, which in turn will spearhead the realization of democratization in an undemocratic country. In short, according to this group the middle class is a major supporter of democratization and democracy in a country.The second mainstream is those who use a contingent or conditional approach. Unlike the first group which considers the causal linearity between social classes as a consequence of modernization and democratization, this second group assumes that the relationship between the middle class and democratization is actually a more dynamic relationship. Bruce Dickson, for example, argues that